Human alveolar lining fluid from the elderly promotes "Mycobacterium tuberculosis" intracellular growth and translocation into the cytosol of alveolar epithelial cells - Olmo-Fontánez, Angélica M.; Scordo, Julia M.; Schami, Alyssa; Garcia-Vilanova, Andreu; Pino, Paula A.; Hicks, Amberlee; Mishra, Richa; Jose Maselli, Diego; Peters, Jay I.; Restrepo, Blanca I.; Nargan, Kievershen; Naidoo, Threnesan; et al. (Mucosal immunology, 2024)
The elderly population is highly susceptible to developing respiratory diseases, including tuberculosis, a devastating disease caused by the airborne pathogen Mycobacterium tuberculosis (M.tb) that kills one person every 18 seconds. Once M.tb reaches the alveolar space, it contacts alveolar lining fluid (ALF), which dictates host-cell interactions. We previously determined that age-associated dysfunction of soluble innate components in human ALF leads to accelerated M.tb growth within human alveolar macrophages. Here we determined the impact of human ALF on M.tb infection of alveolar epithelial type cells (ATs), another critical lung cellular determinant of infection. We observed that elderly ALF (E-ALF)-exposed M.tb had significantly increased intracellular growth with rapid replication in ATs compared to adult ALF (A-ALF)-exposed bacteria, as well as a dampened inflammatory response. A potential mechanism underlying this accelerated growth in ATs was our observation of increased bacterial translocation into the cytosol, a compartment that favors bacterial replication. These findings in the context of our previous studies highlight how the oxidative and dysfunctional status of the elderly lung mucosa determines susceptibility to M.tb infection, including dampening immune responses and favoring bacterial replication within alveolar resident cell populations, including ATs, the most abundant resident cell type within the alveoli.
Gesehen am 07.02.2025